Pregnant Women, a Potential Reservoir for Onchocerca volvulus? A Cross Sectional Study in Maridi County, South Sudan - Chiara Trevisan; Amber Hadermann; Stephen Raimon Jada; Raphael A. Abong; Yak Yak Bol; Joseph N. Siewe Fodjo; Katja Polman; Robert Colebunders (Journal of Epidemiology and Global Health)
Abstract Background Onchocerciasis, a neglected tropical disease (NTD) caused by Onchocerca volvulus, is hyperendemic in many parts of Africa, including South Sudan. Pregnant women may be a parasite reservoir as they are not included in routine ivermectin (IVM) treatments due to unassessed drug safety. In our study we determined the proportion of pregnant women infected with Onchocerca volvulus and assessed the knowledge and practices on IVM use during pregnancy. Methodology/Principal Findings A hospital-based cross-sectional study was conducted in 2023 at Maridi hospital in Maridi County, an onchocerciasis endemic area in South Sudan. All pregnant or one-week post-partum women willing to participate were interviewed, clinically examined, tested with the Ov16 Bioline rapid diagnostic test (RDT) and skin snipped for O. volvulus detection. A total of 317 women aged between 14 and 44 years participated in the study [median age: 23 years (IQR: 19–29)]. Of 290 women who were tested, 179 (61.7%) were Ov16 RDT positive (SD Bioline). Of the 162 women skin snipped, 51 (31.5%) were positive for O. volvulus microfilarial worm following microscopic examination. The microfilaridemia (skin parasite load) ranged between one microfilaria per skin snip (1mf/ss) and 300 mf/ss with a mean value of value of 12.4 (sd: ± 49.1) mf/ss. Most pregnant women (87.8% (274/312)) knew that it was not advised to take IVM during pregnancy. Out of 309 women, 54 (17.5%) had never taken IVM, and 6.4% (16/251) inadvertently took IVM during pregnancy. Of the 16 women who took IVM during pregnancy, 50% (8/16) knew that they were pregnant. Out of 248 women with children, 9 (3.6%) had children suffering from epilepsy; two of them had two children with epilepsy. No abnormalities were reported in the children of the women who took IVM. Conclusions Our study is the first to investigate the prevalence and level of O. volvulus infection among pregnant women in onchocerciasis-endemic areas in Africa. Our results showed a high infection rate of O. volvulus among pregnant women, which may pose a risk for adverse materno-foetal outcomes. Pregnant women in South Sudan are a reservoir for parasite transmission. A clinical trial evaluating the potential beneficial effect of treating O. volvulus infected pregnant women with IVM should be considered, as our preliminary results and the literature suggest that IVM intake might not affect the newborn.